Dasheen—Colocasia esculenta (L.) Schott. - James M. Stephens (EDIS, 2003)
This document provides an overview of dasheen (Colocasia esculenta), a tropical plant cultivated for its edible corms and tubers. It describes the plant’s physical characteristics, cultivation requirements in Florida, and culinary uses. Dasheen thrives in warm, frost-free climates and is typically planted after the last spring frost. The plant’s underground parts are used similarly to potatoes, while its leaves and shoots are edible after proper preparation. The document also highlights traditional dishes made from dasheen, such as calalou and poi. Original publication date May 1994.